Optimizing a woodchip and coal co-firing retrofit for a power utility boiler using CFD. (May 2016) - Gao, Haining; Runstedtler, Allan; Majeski, Adrian; Boisvert, Patrick; Campbell, Doug
Abstract: A computational fluid dynamics (CFD) tool, CFX-TASCflow, with a drag force sub-model for woodchip particles was used to explore the optimization of woodchip co-firing of a Canadian utility boiler, after it was first validated by comparing the model results with field operation data when firing Colombia coal. The CFD model predicted both a small increase in NO emissions and a significant increase in unburned carbon in fly ash for the originally proposed co-firing configuration, with 85% of the unburned carbon originating from the woodchips. Improvement strategies were examined, including intensifying the swirl inside the furnace to improve oxygen availability for woodchip combustion, lowering the woodchip injection level to increase residence time, and reducing woodchip particle size to shorten burnout time. The model results revealed the importance of intensified swirl on the burnout of large woodchip particles and the sensitivity of NO emissions to the air distribution in the combustion zone. Also, the model predicted an increase in large unburned woodchip particles falling into the bottom hopper when lowering woodchip injection level, although there was an overall improvement in predicted woodchip burnout. An improvement in woodchip burnout was also observed with reduced woodchip particle size. Based on these results, a co-firing strategy is suggested that is predicted to give reasonable burnout and NOx emissions at a minimum retrofitting cost. Highlights: Customized woodchip sub models were used in woodchip co-firing CFD simulations. Intensifying swirl improved the burnout of larger woodchip particles. NOx emissions were sensitive to air distribution in the main combustion zone. Lowering woodchip injection level increased particles falling into the bottom hopper. Reducing woodchip size improved burnout.